Penyuluhan Tentang Pelaksanaan Posyandu Sistem 5 Meja Pada Kader Posyandu Bergas Waras kelurahan Sumampir Kecamatan Purwokerto Utara - Netra Wirakhmi, Ikit; Arni Nur Rahmawati (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Posyandu is one form of Community-Based Health Effort (UKBM) managed and organized by, from, and for the community in health development, aiming to empower the community and provide easy access to basic health services to accelerate the reduction of maternal and infant mortality rates. The urgency of this Community Service activity is to optimize the role of cadres at Posyandu Bergas Waras. The objectives of this Community Service Program are: 1) To assess the level of knowledge of posyandu cadres about the 5-table system, and 2) To provide counseling to cadres about the 5-table system in posyandu. The methods used in this activity are: 1) Measuring the level of knowledge of cadres before counseling through a questionnaire, 2) Providing counseling to posyandu cadres about the 5-table system, and 3) Measuring the level of knowledge of cadres after counseling through a questionnaire. The results of this program showed a 40% increase in the cadres' knowledge. Posyandu Bergas Waras cadres are expected to implement the 5-table system in their routine posyandu activities.